Pengaruh Kemudahan Pengguna terhadap Kepuasan Layanan Mobile Banking - Eka Efrika Sari; Fachriandi Saputra; Karina Lestari April Sela Deki; Wanty Eka Jayanti (Jurnal Ekonomi dan Bisnis Digital, 2025)
The rapid development of digital banking services has encouraged banks to provide mobile banking applications that are easy to use and capable of increasing customer satisfaction. However, the perceived ease of use is not always optimal for all users, which can affect the level of service satisfaction received. This study aims to analyze the effect of ease of use on mobile banking service satisfaction among active users in Pontianak City. The research employed a quantitative approach using an explanatory research design. Data were collected through an online survey of 105 respondents who had used mobile banking for at least the past six months. Data analysis was conducted using reliability tests, Pearson correlation, and simple linear regression with the assistance of Microsoft Excel. The results show that ease of use has a positive and significant effect on mobile banking service satisfaction, with a correlation coefficient of 0.889 and an R Square value of 0.790. This indicates that the easier an application is to use, the higher the level of customer satisfaction. This study is expected to serve as a reference for banks in designing more user-friendly mobile banking applications to improve service quality.